Pengaruh Pendidikan Karakter, Kreativitas Belajar dan Motivasi Belajar terhadap Prestasi Belajar Siswa - Aspiani Aspiani; Muh. Ilyas Thamrin Tahir; Andi Annisa Sulolipu; Elpisah Elpisah (Jurnal Ecogen, 2023)
This study aims to determine the effect of Character Education, Learning Creativity and Learning Motivation on Student Achievement in terms of Knowledge and Attitude Values partially and simultaneously as well as the most influential variables. The population is all class XI SMAS Darul Falah Enrekang. Data collection uses a sample selection technique with a non-probability sampling method. Based on predetermined criteria, the sample processed was 64 people who studied Economics with the data collection techniques used were observation, questionnaires and documentation. The data analysis technique used is simple regression analysis and multiple linear regression using SPSS software ver.22.The results of this study indicate that character education, learning creativity and learning motivation partially and simultaneously have a positive effect and the variable character education has the most dominant effect on student learning achievement in terms of knowledge and attitude values in economics subjects.